Tazkiyatun Nafs Menurut Said Hawwa dan Implikasinya dalam Pembentukan Akhlak Mulia - Andini Putri Utami (Bandung Conference Series: Islamic Education, 2024)
Abstract. Noble morals are a necessity for carrying out worship rituals to build a relationship with God and establish social relationships between fellow humans. However, in reality, humans are currently experiencing a crisis of morality and causing bad behavior that can plunge and damage generations. Therefore, the world of education needs a new concept to form the young generation with noble morals through the world of Islamic religious education. According to Said Hawwa, the concept of tazkiyatun nafs is carried out using three methods, including: purifying the heart by eliminating heart disease, adorning oneself with commendable morals and imitating noble morals that come from the names of Allah and the morals of the Prophet Muhammad. The aim of this research is to understand the concept of tazkiyatun nafs according to Said Hawwa and apply the implications of the concept of tazkiyatun nafs according to Said Hawwa in the formation of noble morals. The research method used is a descriptive analytical qualitative research method through literature study data collection. The result of this research is the concept of tazkiyatun nafs according to Said Hawwa, namely cleansing the soul and heart from dirt and disease which causes behavior to reflect disgraceful morals by adorning oneself with righteous deeds, practicing noble morals by imitating the names of Allah and the morals of the Prophet Muhammad. The implication of the concept of tazkiyatun nafs according to Said Hawwa in the formation of morals is to produce humans who have morals towards Allah, towards fellow humans and towards themselves. Abstrak. Akhlak mulia merupakan kebutuhan untuk menjalankan ritual peribadatan untuk membangun hubungan dengan Allah dan menjalin hubungan sosial antar sesama manusia. Namun, pada kenyataannya saat ini manusia mengalami krisis moralitas dan menyebabkan perilaku buruk yang dapat menjerumuskan dan merusak generasi. Oleh karena itu, dunia pendidikan membutuhkan konsep yang baru untuk membentuk generasi muda dengan akhlak mulia melalui dunia pendidikan agama Islam. Konsep tazkiyatun nafs menurut Said Hawwa dilakukan dengan tiga metode, antara lain: menyucikan hati dengan menghilangkan penyakit hati, menghiasi diri dengan akhlak terpuji dan meneladani akhlak mulia yang berasal dari nama-nama Allah dan akhlak yang dimiliki oleh Rasulullah Saw. Tujuan dari penelitian ini adalah untuk memahami konsep tazkiyatun nafs menurut Said Hawwa dan menerapkan implikasi konsep tazkiyatun nafs menurut Said Hawwa dalam pembentukan akhlak mulia. Metode penelitian yang digunakan adalah metode penelitian kualitatif deskriptif analitis melalui pengumpulan data studi literatur. Hasil dari penelitian ini adalah konsep tazkiyatun nafs menurut Said hawwa yaitu membersikan jiwa serta hati dari kotoran dan penyakit yang menyebabkan perilaku mencerminkan akhlak tercela dengan menghiasi diri dengan amal shalih, mengamalkan akhlak mulia dengan meneladani nama-nama Allah dan akhlak Rasulullah Saw. Implikasi pada konsep tazkiyatun nafs menurut Said Hawwa dalam pembentukan akhlak ialah menghasilkan manusia yang berakhlak kepada Allah, kepada sesama manusia dan kepada diri sendiri.